+0  
 
0
77
1
avatar+87 

I keep getting the wrong answer for x and z.... 

 

Can someone help me with the last two... 

 

rrahh  Aug 29, 2018

Best Answer 

 #1
avatar+348 
+2

Since \(x + y + z = 180, x + z = 135\). In the middle triangle, you can see that \(3x = 180\), so \(x = 60\). This means that \(60 + z = 135\) so \(z = 75\).

 

- Daisy

dierdurst  Aug 29, 2018
 #1
avatar+348 
+2
Best Answer

Since \(x + y + z = 180, x + z = 135\). In the middle triangle, you can see that \(3x = 180\), so \(x = 60\). This means that \(60 + z = 135\) so \(z = 75\).

 

- Daisy

dierdurst  Aug 29, 2018

29 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.